Community-based Ecotourism Model for Development UNESCO Global Geopark: A case study of UGG Batur Bali, Ciletuh-Palabuhanratu West Java, and Toba Caldera North Sumatra - Orpha Jane; Gandhi Pawitan (Program Pascasarjana, 2021)
Geopark or the established UNESCO Global Geopark (UGG), such as Toba Caldera, Batur, or Ciletuh, in fact, will stimulate local economic development, such as through ecotourism, by monetizing the potential of their geo-diversity, bio-diversity, and local culture. It is argued that the ecotourism model that involving the local community has great potential in supporting the success of Geoparkâ€™s sustainability. This study contributes as the best practice and guidance in managing the current UGG or developing the next UGG. Hence, this study aims to explore and describe the implementation of Geopark management following a community-based ecotourism model. Three cases study were carried out in UGG Batur, Ciletuh, and Toba Caldera.Â Some aspects were studied, including key stakeholders and their roles, mapping community involvement, and implementation of the CBE in managing the UGG. Focus group discussions were done with resource persons from five main sectors, namely academics, government, community, entrepreneurs, and the media.Â The results show that in most cases, the Geopark sites belong to the community or managed by the community, which is considered as a good condition for stimulating the CBE model. Applying the CBE model effectively requires key actors in the community with soft and hard skill competencies.Keywords: Batur Lake Bali, Ciletuh-Palabuhanratu West Java, Community-based ecotourism, Community involvement, Geopark, Toba Caldera North Sumatera.